The Efficacy of Restorative Justice Programs in Reducing Recidivism Rates - Ahidjo, Nayah (International Journal of Humanity and Social Sciences, 2024)
Purpose: This study sought to assess the efficacy of restorative justice programs in reducing recidivism rates. Methodology: The study adopted a desktop research methodology. Desk research refers to secondary data or that which can be collected without fieldwork. Desk research is basically involved in collecting data from existing resources hence it is often considered a low cost technique as compared to field research, as the main cost is involved in executive's time, telephone charges and directories. Thus, the study relied on already published studies, reports and statistics. This secondary data was easily accessed through the online journals and library. Findings: The findings reveal that there exists a contextual and methodological gap relating to restorative justice programs in reducing recidivism rates. Preliminary empirical review revealed that restorative justice interventions were effective in reducing reoffending and promoting positive outcomes for both offenders and victims. Through processes such as victim-offender mediation and family group conferencing, restorative justice provided opportunities for offenders to take responsibility, repair harm, and engage in rehabilitation. While acknowledging variations in effectiveness based on offender characteristics and program implementation, the study highlighted the importance of continued investment in restorative justice initiatives to create a more just and equitable criminal justice system. Unique Contribution to Theory, Practice and Policy: Labeling theory, Social Learning theory and Routine Activities theory may be used to anchor future studies on restorative justice programs in reducing recidivism rates. The study offered recommendations that contributed to theoretical advancements, practical improvements, and policy developments in the field. It emphasized the importance of exploring underlying mechanisms, standardized training for practitioners, and integration of restorative principles into mainstream criminal justice policies. These recommendations were aimed at enhancing the effectiveness and sustainability of restorative justice interventions in promoting positive outcomes for victims, offenders, and communities.